The Physicochemical and Structural Characteristics of Cultivated Sahlep - Abdullah Kurt; Talip Kahyaoglu (International Journal of Secondary Metabolite)
Sahlep is obtained from tubers of orchids which grown in Mediterranean countries, especially in Turkey. As hydrocolloid, it is used for preparing hot drink and ice cream. However, orchid plants are damaged and sold with high priced. Therefore, searching of alternative production methods of sahlep are in progress. The products of the project, growing possibilities of sahlep orchids at farm conditions (cultivation) were researched in this study. The naturally grown sahlep which belongs to Serapias vomeracea and Orchis sancta species compared with that of cultivated products. Physicochemical and structural characterization analyses were performed for the samples. The tubers were obtained from Serapias vomeracea exhibited higher similarity in physicochemical properties with naturally grown one than Orchis sancta. Samples have Newtonian flow behavior. FTIR experiments which provide knowledge about chemicals bonds in structure revealed that cultivation studies have no effect on sahlep chemical structure. Amorph structure was determined with the XRD experiment for all samples. The variation of surface morphology of sahlep was observed with the cultivation by SEM. DSC and TGA analysis exhibited that samples had similar thermal stabilities. The results obtained showed that sahlep with the same physicochemical and structural characteristics with naturally grown could be achieved by cultivation. The development and widening in this production method provides both protection of wild orchids and cheaper sahlep production.